Microstructure and mechanical properties of FeCoCrNiMnAlx high-entropy alloys prepared by mechanical alloying and hot-pressed sintering - Cheng, Hu; Liu, Xiaoqiang; Tang, Qunhua; Wang, Weiguo; Yan, Xiaohui; Dai, Pinqiang (Journal of alloys and compounds, 2019)
To improve the strength and hardness, Al-containing FeCoCrNiMn high-entropy alloys (HEAs) were fabricated by mechanical alloying (MA) and hot-pressed sintering. The effects of Al concentration on the microstructure and mechanical properties of the alloys were examined. It was found that the Al-containing alloys consisted of the matrix fcc or fcc + bcc duplex solid solution phases and a small quantity of M7C3 + M23C6 (where M = Cr, Mn, Fe) carbides and Al2O3 phases. A high Al concentration induced bcc precipitates in the alloys, and with the increase of Al concentration, the crystalline structure of the matrix solid solution phase changed from fcc to bcc. The addition of Al obviously strengthened the alloys, especially the alloys that contained fcc + bcc duplex solid solution phases. For example, the yield strength, compressive strength and hardness of alloy FeCoCrNiMnAl0.7 reached as high as 2230 MPa, 2552 MPa and 622 HV, respectively. The high strength/hardness was attributed mainly to the finer grains and the bcc precipitation. •The FeCoCrNiMnAlx high-entropy alloys were prepared by powder metallurgy.•The existing criteria cannot fully predict the crystal structure of the alloys.•The addition of Al obviously strengthened the alloys.•The high strength was attributed mainly to the finer grains and bcc precipitation.